China Merchants in Djibouti: from the maritime route to the digital silk route - (:unkn) unknown (My University, 2018)
The determination of Chinese groups to become uncontested leaders in all activities related to maritime transport is proven. Two cases are particularly noteworthy, the best-known and best-documented being probably COSCO and the port of Piraeus. On the other hand, that of China Merchants in Djibouti, still poorly understood, will be the subject of our contribution. We will not deal with security aspects (establishment of a naval base) – largely dealt with elsewhere – but will favour economic and commercial aspects (establishment of China Merchants). The two logics can meet, but they respond to very different strategies: a national strategy to assert China's military power as opposed to a corporate strategy to consolidate its global role. Djibouti's dream of becoming a "commercial hub" and an "East African Singapore", gives a particular dimension to China Merchants' choice because it is not the result of the Chinese government's will, but of a specific request from the Djiboutian government. Our research will be conducted on the basis of existing documents, whether official reports, scientific studies or more journalistic information. It will favour first-hand Chinese documents.
Keywords: African Research